Single nucleotide polymorphism, haplotypes and genotypes of Mannose-binding lectin (MBL1) gene and their association with clinical mastitis in Murrah buffalo - Shergojry, Shahid Ahmad; Verma, Archana; Gupta, Ishwar Dayal; Mir, Nazir Ahmad (Buffalo Bulletin, 2023)
The Mannose-binding lectin (MBL1) gene is an important component of immune response system. It plays vital role in activation of the complement system and act as chief defense molecule of host cell to provide protection against various diseases. In the recent study, six novel single nucleotide polymorphisms (SNPs), at 2689G>C, 2751A>G, 4822T>C, 4853A>G, 4855T>C, and 4978T>C resulted in 2 non synonymous type of change at 4853A>G, 4855T>C resulting in one amino acid substitution Ser150Gly of MBL1 protein and their association with clinical mastitis were investigated in two hundred (200) Murrah buffaloes. These SNPs in MBL1 were genotyped by using the polymerase chain reaction (PCR) and Deoxyribose nucleic acid (DNA) sequencing methods in order to reveal the association with clinical mastitis. SHEsis software tool was used for construction of haplotypes and Linkage disequilibrium analysis. Twenty one (21) haplotypes were constructed. Allelic association analysis showed that C allele of 2689 G>C, A allele of 2751 A>G, C allele of 4822 T>C, A allele of 4853 A>G, C allele of 4855 T>C, and C allele of 4978 T>C had significant association with increased risk of clinical mastitis in Murrah buffaloes (P<0.05). Murrah buffaloes with CG genotype of 2689 G>C, AG or GG genotype of 2751 A>G, CC genotype of 4822T>C, AG or GG genotype of 4853 A>G, TC or CC genotype of 4855 T>C and CC genotype of 4978 T>C loci had significantly lower incidence of clinical mastitis compared to their counter genotypes. Haplotype association analysis showed that Hap21 (TATTGA) was found significantly related to higher risk of clinical mastitis (P<0.05). Hap14 (TGTTGG) and Hap5 (CGCCCA) were found significantly associated with lower risk of clinical mastitis in Murrah buffalo (P<0.05).